Hedging System Of Modal Auxiliary On English As Foreign Language (EFL) Journal Papers - Harlinah Sahib; Kusmianti Rahayu MH (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2022)
The study of hedging phenomenon is updating, indicating that the essence and interest take the attention among the researchers especially in the researchers from Indonesia. This research aimed to examine hedging system of modal auxiliary on English as Foreign Language (EFL) research papers. The present study investigated hedges system of research papers from the fields of EFL journal papers. It comprised 15 articles written by Indonesian writer-researchers taken from TEFLIN. The papers uploaded to lancsbox 6,0, corpus software. The analysis is not relied on the software only, but also manual checked to see the context in measuring the hedging. This study Applied quantitative method, the data analysis reveals major results. The results show that EFL researchers utilized more hedges by 64 pttw. Hedges employed in the form of Modal auxiliary appeared as the most frequent hedge occurred in discipline. To conclude, EFL researchers of Indonesia is employing hedges to accommodate the claims.